The Role of Changes in Customer Behavior on Smart Marketing Strategies in The Post-Covid Pandemic Era - Maria Sugiat (UniSadhuGuna Business School, 2021)
Introduction: At the beginning of 2020 COVID-19 virus swept the globe in a matter of months, jeopardizing lives, upending businesses, and setting off a worldwide economic slump. To suppress the spread of Covid-19, the government of Indonesia implemented